Phosphate ion sensor fabrication based on conductive polymer polypyrrole film coatings in doped phosphate using thick film technology - Nofriyani Nofriyani; Robeth Viktoria Manurung; Aminuddin Debataraja; Indra Dwisaputra (National Research and Innovation Agency, 2021)
This study describes the development of chemical sensors to detect polypyrrole (PPy) based phosphate sensors in doped di-ammonium hydrogen phosphate (DAP) with thick film technology (TFT). Manufacturing screen-printed carbon electrode (SPCE) with thick film uses alumina substrate provided a more portable, miniature, inexpensive, and reduced use of samples and reagents. Polymer polypyrrole and di-ammonium hydrogen phosphate as sensitive membranes are electrodeposition on carbon electrodes. Characterization has been conducted to see the electrode morphology in scanning electron microscopy (SEM) test, which showed that sensitive material particles were distributed evenly on the surface of the sample and spherical. The energy dispersive spectroscopy (EDS) experiment results showed the atomic composition respectively carbon 86.95 %, nitrogen 6.94 %, oxygen 5.9 %, and phosphate 0.21 %, which were exposed to the electrode. The performance test of electrodes with a phosphate standard solution has proceeded at a concentration between 5 to 100 mg/l, which is measured using the galvanostatic method. The voltage range was from 0.252 to 0.957 V with R2 at approximately 90.265 %. The results of sensor performance were concluded that the electrode was able to detect phosphate ions.